2012
DOI: 10.1007/s00268-012-1589-x
|View full text |Cite
|
Sign up to set email alerts
|

Is Intravenous Iron Useful for Reducing Transfusions in Surgically Treated Colorectal Cancer Patients?

Abstract: Intravenous iron does not appear to reduce the blood transfusion requirements in the postoperative period of colorectal surgery patients with anemia. We consider that further studies are needed to more clearly define the usefulness of intravenous iron in reducing the transfusion needs in such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…In all these studies, patients were anemic before treatment (mean Hb level at baseline 9.5 g %) and in all the level of Hb was reevaluated after therapy (in most after a month). With only one exception [22], a statistically significant increase of the Hb level was observed (mean Hb increase: 1.6 g %). That increase of the Hb level was clearly superior to that observed in controls in two studies [18,19].…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…In all these studies, patients were anemic before treatment (mean Hb level at baseline 9.5 g %) and in all the level of Hb was reevaluated after therapy (in most after a month). With only one exception [22], a statistically significant increase of the Hb level was observed (mean Hb increase: 1.6 g %). That increase of the Hb level was clearly superior to that observed in controls in two studies [18,19].…”
Section: Discussionmentioning
confidence: 83%
“…In most of the studies reported here, no sufficient data are provided to separate between absolute and functional iron deficiency and it is likely that the iron deficiency anemia was multifactorial in many patients, namely blood losses in the surgical series [17,19,21,22]. Therefore, it is not surprising that iron supplementation was effective, although the only negative study [22] was conducted in operated colon cancer patients.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations